Bridging worlds with words: translanguaging and its impact on identity formation among Jordanian graduate students in Ontario - Almashour, Mohamad (Frontiers in Education, 2024)
Translanguaging, an approach to multilingualism, enables individuals to draw from their entire linguistic repertoires, challenging traditional language boundaries. This study explores how translanguaging practices influence identity formation, academic integration, and social adaptation among Jordanian graduate students in Ontario, Canada, where linguistic diversity and bilingualism present unique challenges and opportunities for cultural expression. A qualitative research design was used, involving semi-structured interviews with 10 Jordanian graduate students who identify as bilingual in Arabic and English. Data were collected through interviews conducted in both languages, ensuring comfort and authenticity in participants’ responses. Thematic analysis was applied to identify patterns in translanguaging practices and their perceived impacts on identity and academic experiences. Findings indicate that translanguaging facilitates identity expression, allowing students to bridge their Jordanian heritage with their new Canadian academic environment. Participants reported enhanced comprehension of academic material, improved confidence in class participation, and increased social cohesion through linguistic flexibility. However, they also highlighted challenges, including experiences of linguistic stereotyping and a lack of institutional support for multilingual practices. The study underscores translanguaging as a critical tool for identity negotiation, academic success, and social integration, advocating for educational policies that acknowledge and support its value in multicultural and multilingual settings. The implications highlight the need for inclusive language practices in higher education to foster belonging, respect for linguistic diversity, and academic achievement among international students.